EFEKTIVITAS PIJAT EFFLEURAGE DAN COUNTERPRESSURE TERHADAP KEMAJUAN DILATASI SERVIKS PADA KALA I FASE AKTIF - Nirmala Santiasari, Retty; Siti Nurdiati, Detty; Lismidiati, Wiwin (MEDIA ILMU KESEHATAN, 2018)
Backgraound: Labor process begins with the process of cervical dilatation, which is commonly accompanied by pain. Labor pain caused by uterine contractions can cause thinning of the cervix. Effects of labor pain includes inflammation in uterus and labor dystocia. Effleurage and counterpressure are complementary treatment to stimulate uterine contractions. Objective: To analyze the effectiveness of effleurage and counterpressure massages on the progress of cervical dilatation. Method: This was a quasi-experiment study with pre-post test nonequivalent control group. Population was the women in labor in stage I active phase. Research subjects were 68 people that were divided into two groups. Sampling technique was consecutive sampling. Instrument used in this study was the internal examination. Data were analyzed using Wilcoxon and Mann Whitney. Results: The progress of cervical dilatation before and after the intervention of the effleurage was 4.74±0.83 vs 7.47±1.21 with p=0.00 and the result for the counterpressure group was 4.59±0.66 vs 8.03±0.96 with p=0.00. The average improvement of cervical dilatation on the effleurage and counterpressure groups was 2.73 vs 3.44 with p=0.00. Conclusion: The counterpressure has the more significant effect than the effleurage on improving the cervical dilatation. Keywords: Cervical dilatation, counterpressure, effleurage